A Multicenter Retrospective Study on the Prognosis of Stage III Unresectable Mutant Non-Small Cell Lung Cancer With Tyrosine Kinase Inhibitors Therapy - Wu, Ranpu; Yu, Shaorong; Ye, Jinjun; Wang, Yimin; Zhao, Zhiting; Liu, Hongbing; Song, Yong (Frontiers in Oncology, 2021)
Background: For unresectable stage III non-small cell lung cancer (NSCLC), concurrent chemoradiotherapy is nowadays the standard treatment. Patients with advanced NSCLC harboring driver-gene mutations benefit from Tyrosine Kinase Inhibitors (TKIs) Therapy. In a real-world setting, there is room for exploring the benefit of TKIs in stage III unresectable NSCLC patients with mutation. Methods: A total of 81 patients from Jinling Hospital and Jiangsu Cancer Hospital with stage III unresectable mutant NSCLC applied targeted therapy were enrolled in this retrospective study. Patients with first-line application of TKIs were followed up to gain the situation of surgery qualifications, progression-free survival and overall survival, so as to evaluate the survival prognosis, then whether patients benefit and what kind of patients benefit most from TKI monotherapy treatment or its combination are explored. Results: The median progression-free survival of involved 81 patients was 13.87 months (95% confidence interval (CI): 11.66-16.08), and the median survival was 41.47 months (95%CI: 20.11-62.83). The 5-year survival rates were 91.0%, 80.3%, 56.1%, 45.5%, 32.5%, respectively. After first-line TKI therapy, 7 patients (8.6%) were reevaluated as eligible for surgery and proceeded to surgery. Although no characteristics were found to be statistical prognostic, younger female non-smokers still tended to have a better prognosis with longer progression free survival and overall survival. Conclusions: TKIs are a viable option for mutant stage III unresectable NSCLC patients who have achieved good clinical benefit from TKI. Patients who cannot tolerate chemoradiotherapy, especially those with driver gene mutations, can choose targeted therapy for first-line treatment.